REMAKING EDUCATION WITH THE HELP OF INFORMATION AND COMMI.:JNICATION - García Toledo, Magdalena (2008)
This article evaluares an educational experience assessing information andcomunicaction technologies. Not only education of values and the methodologywhich ensues from this experience are considered important assets, but also the useof Internet technologies.In the first part so me concepts about the way in which information and communicationhave changed educational paradigms throuhg the fostering of interactivity, interpersonaland group communication and the making of knowledge centered in the student aredeveloped. The second part is the description of the experience.